Efficacy of Second-Line Chemotherapy in Extrapulmonary Neuroendocrine Carcinoma. Issue 4 (April 2020) - McGarrah, Patrick W.; Leventakos, Konstantinos; Hobday, Timothy J.; Molina, Julian R.; Finnes, Heidi D.; Westin, Gustavo F.; Halfdanarson, Thorvardur R.
Abstract : Objectives: A platinum/etoposide doublet is standard first-line therapy for poorly differentiated neuroendocrine carcinoma (PD NEC); however, evidence to guide treatment beyond first-line regimens is lacking. This study aimed to evaluate the efficacy of second-line regimens in PD NEC. Methods: We performed a retrospective analysis of patients treated with second-line chemotherapy for PD NEC. Inclusion criteria were previous first-line therapy with platinum/etoposide, extrapulmonary PD NEC, and follow-up data. The primary end points were overall survival (OS) and progression-free survival (PFS) after second-line therapy. Secondary end points included OS and PFS from first-line therapy. Results: Sixty-four patients were included. The median OS from initiation of second-line therapy was 6.2 months (95% confidence interval [CI], 4.9–8.9). The median PFS was 2.3 months (95% CI, 2.0–3.2). No second-line regimen showed a statistically significant difference in OS or PFS. There was a significant increase in OS for cisplatin first-line regimens compared with carboplatin (17.0 months [95% CI, 12.5–22.6] vs 11.7 months [95% CI, 8.0–14.0]). Conclusions: The efficacy of current second-line therapy in PD NEC is poor. No second-line regimen showed statistically significant superiority. Cisplatin was associated with longer OS regardless of second-line regimen or age. However, unmeasured confounders such as performance status or comorbidities may explain this effect. Abstract : Supplemental digital content is available in the text.